2006
DOI: 10.1182/blood-2005-11-4757
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of a murine model of adult T-cell leukemia using 211At-7G7/B6 and its combination with unmodified anti-Tac (daclizumab) directed toward CD25

Abstract: IntroductionAdult T-cell leukemia (ATL) develops in a small portion of individuals infected with human T-cell lymphotrophic virus-1 (HTLV-I) and consists of an overabundance of malignant activated T cells, which are characterized by expression of the ␣ subunit of the interleukin-2 receptor (IL-2R␣; CD25) on their cell surfaces. [1][2][3][4] Presently, there is no accepted curative therapy for ATL and patients progress to death with a median survival duration of 9 months for those with acute ATL and 24 months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Radionuclides emitting ␣-particles have a high linear energy transfer (6-to 9-MeV particles) that act over 10-80 m and are effective at killing individual target cells (39). We have demonstrated that 211 At-labeled 7G7/B6, an anti-CD25 monoclonal antibody, was very effective in the treatment of murine models of leukemia (36,40). A phase I clinical trial with 213 Bi-HuM195 in the treatment of patients with relapsed and refractory acute or chronic myelogenous leukemia was reported to show promising results (41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Radionuclides emitting ␣-particles have a high linear energy transfer (6-to 9-MeV particles) that act over 10-80 m and are effective at killing individual target cells (39). We have demonstrated that 211 At-labeled 7G7/B6, an anti-CD25 monoclonal antibody, was very effective in the treatment of murine models of leukemia (36,40). A phase I clinical trial with 213 Bi-HuM195 in the treatment of patients with relapsed and refractory acute or chronic myelogenous leukemia was reported to show promising results (41).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that 211 At linked to the anti-CD30 monoclonal antibody, HeFi-1, provided effective therapy for the karpas299 leukemia model. A paradigm is emerging in monoclonal antibody-mediated treatment that therapeutic efficacy may be augmented through the use of two agents with different modes of action (30)(31)(32)(33)(34)(35)(36). In this study, we used 211 At-HeFi-1, which causes radiation damage to the tumor cells, followed by the administration of receptor-saturating doses of unmodified HeFi-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in BIRC5 (survivin) expression in ATLL may play a role in cell survival by inhibiting apoptosis and is associated with resistance to chemotherapy and poor prognosis. CD25 (TAC) tends to be highly expressed in ATLL, and attempts have been made to target this using monoclonal antibody-toxin conjugates [74][75][76]. More recently, CCR4 (chemokine receptor 4) expression has been reported to be frequent in ATLL [77] and may account for the frequent infiltration of the lymphoma in skin and lymph nodes.…”
Section: Peripheral T-cell Lymphomasmentioning
confidence: 99%